Transnational Social Protection: Inclusion for Whom? Theoretical Reflections and Migrant Experiences - Scheibelhofer, Elisabeth (2022)
With migration being a reality within and between nation‐states worldwide, transnational social protection has become a concern on various levels. This thematic issue focuses on nation‐state conceptions and policies, migrants’ experiences with regards to accessing social protection, as well as the social inequalities resulting from the nexus of transnational social protection and migration.